Evaluasi Penerapan Sistem Informasi Akuntansi Pendapatan Kas Terhadap Pengendalian Intern pada Pemandian Air Panas Pariban - Ela Vani Ginting; Mulatua P. Silalahi; Rimky Mandala P. Simanjuntak (Jurnal Ilmiah METHONOMI, 2024)
In information systems accounting income cash and internal control there needs to be a good procedure in a company that has been set. The gap between any duty unit-unit organization to separate functions, duty, and responsibilities of each employee as, parking lot, ticketing, café, restaoran, and lodging. Cash income is computerized so that the company can know the amount of income each month because it is able to present data on each income and expenditure transaction completely and accurately. The purpose of this study is to find penelitin how accounting of this information in at pariban hot springs . And to know that the implementation of the internal control have walked with the applicable regulation or not. Research sites as the object of this research is in pariban hot springs. Review at this research is cash income. Method collection method used is research filed literature and methods. And the method of analysis of data on research kualitatif this is the method. Based on the discussion this research result we can conclude that the system of cash revenues at pariban hot springs systematically has been running well. The event bagian-bagian selling transaction services have been able to coordinate well in completing the transaction.